Pengaruh Pengetahuan, Sikap dan Tindakan Masyarakat Terhadap Konsep Rumah Sehat Di Kawasan Industri Medan Kecamatan Medan Deli - Alma, Arlin Liliana; Pakpahan, Eka Lolita Elivanti; Ginting, Rapael (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of knowledge, attitudes, and community actions on the concept of healthy homes in Medan Industrial Estate, Medan Deli Sub-district. This study used a quantitative approach with a cross-sectional analytic design and random sampling technique involving 100 respondents. The data obtained were then analyzed using the chi-square test to test the influence between the variables of knowledge, attitudes and actions with the concept of healthy homes. The results showed that there was a significant influence between the variables of knowledge (p-value = 0.004), attitude (p-value = 0.016), and action (p-value <0.001) of the community with the concept of healthy homes in Medan Industrial Estate. The majority of respondents had good levels of knowledge, attitudes, and actions in supporting the creation of healthy homes, which were also supported by the physical condition of homes that meet environmental health requirements. Based on these findings, the study recommends the need for collaboration and support from various relevant parties including the government and non-governmental organizations to improve education and public awareness on the importance of healthy housing concepts, so as to expand the implementation of healthy homes in a sustainable manner in Medan Industrial Estate and surrounding areas.